2020
DOI: 10.1080/00036846.2020.1752899
|View full text |Cite
|
Sign up to set email alerts
|

Lagged country returns and international stock return predictability during business cycle recession periods

Abstract: This study examines stock return predictability in business cycle fluctuations across 17 developed countries and 26 developing countries over the period from January 1970 to December 2019. We uncover that lagged U.S. returns can be regarded as a reliable predictor only during recessions. The results remain robust after controlling for commonly used return predictors. Our empirical findings carry some implications for the role of leading markets, fundamental uncertainty, change in investors' beliefs and dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Many studies find that stock return predictability is sensitive to business cycles, as the variation in economic conditions will influence investor behavior and will eventually drive stock returns (Andrei et al , 2019; Racicot and Théoret, 2019; Wen and Li, 2020). Moreover, the relationship between higher moments contained in hedge funds and future returns has an asymmetric effect over the business cycles (Gregoriou et al , 2020; Racicot and Théoret, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Many studies find that stock return predictability is sensitive to business cycles, as the variation in economic conditions will influence investor behavior and will eventually drive stock returns (Andrei et al , 2019; Racicot and Théoret, 2019; Wen and Li, 2020). Moreover, the relationship between higher moments contained in hedge funds and future returns has an asymmetric effect over the business cycles (Gregoriou et al , 2020; Racicot and Théoret, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Alessi and Detken (2011) found that the global measures of liquidity are the best indicators of asset price cycles as opposed to domestic monetary and credit conditions. Additionally, the cross-country influence between stock prices may arise from at least two channels: the impact of monetary policy conducted abroad (Bhattarai et al, 2021;Kolasa & Wesołowski, 2020) and the link between stock prices in different countries (Wen & Li, 2020;Tang et al, 2019), among other channels.…”
Section: Datamentioning
confidence: 99%
“…Predicting stock market returns has long been of interest to academics, policy makers and practitioners in finance. Numerous studies have examined the predictability of stock market returns around the world, yet the robustness of predictions remains unresolved (see Li et al, 2020;2022;Wen and Li, 2020). The need to predict changes in stock returns in international financial market has become essentially important in the wake of growing financial globalization, as robust predictions enable investors to minimize their risks and losses.…”
Section: Introductionmentioning
confidence: 99%